EVALUATING GENERATIVE ARTIFICIAL INTELLIGENCE AND INTERNET SEARCHES IN FOREIGN LANGUAGE GRAMMAR LEARNING: EXAMINING THE ROLE OF EXPERTS THROUGH A STUDY ON VOCABULARY BEGINNING WITH “MER-” IN MALAY - Murata, Yumie (Universitas Terbuka, 2023)
This study aimed to clarify the usefulness and limitations of generative artificial intelligence (AI) and online information in the self-study of foreign languages, and to reassess the domain of roles that humans, such as language teachers and experts, should perform. As a learner of Malay, the author attempted to pursue this objective by seeking solutions to grammar-related questions that arose during the process of learning Malay without directly asking teachers or specialists, instead posing questions to generative AI or conducting Internet searches. The author first pursued the question of using the form